Characterization of degradation products of Ivabradine by LC‐HR‐MS/MS: a typical case of exhibition of different degradation behaviour in HCl and H2SO4 acid hydrolysis. (2nd February 2015) - Patel, Prinesh N.; Borkar, Roshan M.; Kalariya, Pradipbhai D.; Gangwal, Rahul P.; Sangamwar, Abhay T.; Samanthula, Gananadhamu; Ragampeta, Srinivas
Abstract : A validated stability‐indicating HPLC method was established, and comprehensive stress testing of ivabradine, a cardiotonic drug, was carried out as per ICH guidelines. Ivabradine was subjected to acidic, basic and neutral hydrolysis, oxidation, photolysis and thermal stress conditions, and the resulting degradation products were investigated by LC‐PDA and LC‐HR‐MS/MS. The drug was found to degrade in acid and base hydrolysis. An efficient and selective stability assay method was developed on Phenomenex Luna C18 (250 × 4.6 mm, 5.0 µm) column using ammonium formate (10 mM, pH 3.0) and acetonitrile as mobile phase at 30 °C in gradient elution mode. The flow rate was 0.7 ml/min and detection wavelength was 286 nm. A total of five degradation products (I‐1 to I‐5) were identified and characterized by LC‐HR‐MS/MS in combination with accurate mass measurements. The drug exhibited different degradation behaviour in HCl and H2 SO4 hydrolysis conditions. It is a unique example where two of the five degradation products in HCl hydrolysis were absent in H2 SO4 acid hydrolysis. The present study provides guidance to revise the stress test for the determination of inherent stability of drugs containing lactam moiety under hydrolytic conditions. Most probable mechanisms for the formation of degradation products have been proposed on the basis of a comparison of the fragmentation pattern of the drug and its degradation products. In silico toxicity revealed that the degradation products (I‐2 toI‐5 ) were found to be severe irritants in case of ocular irritancy. The analytical assay method was validated with respect to specificity, linearity, range, precision, accuracy and robustness. Copyright © 2015 John Wiley & Sons, Ltd.